2007
DOI: 10.1186/1471-2261-7-15
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus inhibits key events of restenosis in vitro/ex vivo: evaluation of the clinical relevance of the data by SI/MPL- and SI/DES-ratio's

Abstract: Background: Sirolimus (SRL, Rapamycin) has been used successfully to inhibit restenosis both in drug eluting stents (DES) and after systemic application. The current study reports on the effects of SRL in various human in vitro/ex vivo models and evaluates the theoretical clinical relevance of the data by SI/MPL-and SI/DES-ratio's.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Interestingly, we did not detect a critical difference in lumen coverage, apoptosis or activation of the vessel wall in the two culture systems. This is not completely unexpected as the static culture was designed to replicate the vessel ring culture, with tissue specimens of 2-5mm in length (5,21-23). Previous studies have demonstrated that static culture of rings can be extended up to 56 days, and can be induced to form neointima post-injury, although we did not detect such a growth in our samples (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, we did not detect a critical difference in lumen coverage, apoptosis or activation of the vessel wall in the two culture systems. This is not completely unexpected as the static culture was designed to replicate the vessel ring culture, with tissue specimens of 2-5mm in length (5,21-23). Previous studies have demonstrated that static culture of rings can be extended up to 56 days, and can be induced to form neointima post-injury, although we did not detect such a growth in our samples (22).…”
Section: Discussionmentioning
confidence: 99%
“…Besides the obvious ethical concerns, small rodent experiments have limited predictive capacity, resulting in the development of sub-optimal therapeutic strategies, leaving this critical medical need unmet (4). In vitro strategies for the study of vascular remodeling focus on 2D culture of vascular cells (typically smooth muscle cells) or the static culture of rings obtained from blood vessels, the latter importantly incorporates an element of intact extracellular matrix component, which is critical in the remodeling process (for an example (5)). Interestingly, some groups have demonstrated the successful use of flow bioreactors simulating the in vivo hemodynamic conditions, to culture blood vessels ex vivo and study vascular pathophysiology (69).…”
Section: Introductionmentioning
confidence: 99%
“…drug eluting stents (DES’s) or other local devices [26,27]. Recently our group has suggested to calculate a SI/DES ratio [12] for appropriate dosing in DES’s. Due to the fact that agents are commonly underdosed after systemic administration [11] and overdosed in DES’s [12], we would like to suggest SI/MPL- and SI/DES-ratio’s of 1/100 as an orientation.…”
Section: Discussionmentioning
confidence: 99%
“…The SI/MPL-ratio was calculated in order to describe the relation between a significant inhibitory effect in vitro and the maximal plasma level after systemic administration in vivo [11,12]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation